Prevalence of Psychological Distress among Secondary School Teachers in Kiambu County, Kenya - Gakinya, Grace; Wasanga, Christine; Kipnusu, Robert (International Journal of Psychology, 2024)
Purpose: This study sought to “establishtheprevalenceofpsychologicaldistressamongsecondaryschoolteachersinKiambuCounty,Kenya.” Methodology: This study used a quasi-experimental research design. This study was carried out among selected teachers in secondary schools in Kiambu County. Kiambu County has a total of 303 secondary schools with a population of 3,617 teachers (County Government of Kiambu12 sub counties, however the target population will be the teachers in Thika town Sub County. Multistage sampling technique was used at three levels; sampling stage level one was used for selecting the schools at county level where Thika town Sub County was selected. The final overall sample size of 120. The study used the Depression, Anxiety and Stress Scale - 21 Items (DASS-21).Data was collected using questionnaire. Statistical Package for Social Sciences (SPSS) version 21 was used to analyse the data. Data was presented in form of tables. Findings: The results revealed that majority of the respondents (50.5%) had moderate levels of depression meaning that over half of the respondents fell into this category. For anxiety, majority of the respondents (31.8%) had moderate levels of anxiety. For stress, majority of the respondents (68.2%) had normal levels of stress. Unique Contribution to Theory, Practice and Policy: The study used the Cognitive Behavioral Therapy approach. There should be regular monitoring and evaluation of teachers' mental health and well-being within school settings. This can involve implementing surveys or assessments to gauge levels of psychological distress over time and to track the effectiveness of interventions such as cognitive restructuring.